Morphological engineering of silicon nitride hollow fiber membrane for oil-field-produced-water treatment. Issue 8 (1st June 2019) - Abadikhah, Hamidreza; Wang, Jun-Wei; Khan, Sayed Ali; Xu, Xin; Agathopoulos, Simeon
Abstract: Morphological engineering of silicon nitride (Si3 N4 ) hollow fiber membrane was carried out by considering hydrodynamic viscous fingering phenomena, which govern the formation of the finger-like micro-voids layer in membranes. The influence of the solvent, the air gap, and the rate of internal coagulant on the finger-like/spongy layer thickness ratio, porosity, bending strength, pore size distribution, and water permeation, was thoroughly investigated. The viscosity of the suspension played an important role in the development of the microstructure. Membrane morphology can be controlled by optimizing fabrication parameters in order to achieve the desirable fiber structure for the final functional application. The membrane used in microfiltration tests was produced by using N-methyl-2-pyrrolidone (NMP) as a solvent, with an air gap of 5 cm, and an internal coagulant rate of 10 mL⋅min −1 . The membranes comprised a selective finger void-free spongy layer on the outer surface, and displayed high permeation features. The membranes successfully treated highly concentrated (21000 ppm) oil-field-produced-water, and an oil rejection of 95% as well as a stable permeate flux of 480 L m −2 h −1 were achieved. Highlights: Viscous fingering phenomena allowed morphological control of Si3 N4 membranes. The type of solvent, air gap, and internal coagulant rate were influential factors on membrane morphology. The optimized Si3 N4 membranes were successfully used in microfiltration water treatment.